Complications of cold versus hot snare polypectomy of 10–20 mm polyps: A retrospective cohort study. Issue 2 (18th August 2019) - Ket, Shara N; Mangira, Dileep; Ng, Allysia; Tjandra, Douglas; Koo, Ja H; La Nauze, Richard; Metz, Andrew; Moss, Alan; Brown, Gregor
Abstract : Background and Aim: Cold snare polypectomy is safe and efficacious for removing polyps <10 mm with reduced rates of delayed postpolypectomy bleeding and postpolypectomy syndrome. This technique can also be used for sessile polyps ≥10 mm; however, further evidence is required to establish its safety. The aim of this study was to compare intraprocedure and postprocedure adverse events in patients who underwent cold (CSP) versus hot snare polypectomy (HSP) of 10–20 mm sessile colonic polyps. Methods: Electronic medical records and endoscopy reports of all patients who underwent polypectomy for Paris 0‐IIa, Is, or 0‐IIa + Is 10–20 mm colonic polyps between January 2015 and June 2017 at three tertiary academic hospitals and one private hospital were retrospectively reviewed. Data on patient demographics, polyp characteristics, method of polypectomy, and intraprocedural and postpolypectomy adverse events were collected. Results: A total of 408 patients (median age 67, 50% male) had 604 polyps, 10–20 mm in size, removed. Of these, 258 polyps were removed by HSP, with a median size of 15 mm (interquartile range [IQR] 12–20), compared to 346 polyps that were removed by CSP, with median size of 12 mm (IQR 10–15), P < 0.001. In the HSP group, 15 patients presented with postprocedure complications, including 11 with clinically significant bleeding, 2 with postpolypectomy syndrome, and 2 with abdominal pain. This compares with no postpolypectomy complications in the CSP group, P < 0.001. Conclusion: In this study, CSP was not associated with any postpolypectomy adverse events. CSP appears to be safer than HSP for removing 10–20 mm‐sized sessile polyps. A prospective multicenter study has been commenced to verify these findings and to assess the efficacy of CSP for the complete resection of polyps of this size. Abstract : Cold snare polypectomy of 10–20 mm sessile polyps is safe, and no complications were seen when compared with hot snare.